1999
DOI: 10.1001/archfami.8.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physician Perceptions of the Nurse Practitioner in the 1990s

Abstract: The association between previous experience with a primary care NP and a more positive attitude toward NPs has important implications for the training of primary care physicians, particularly in community-based, multidisciplinary settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
2
10
0
1
Order By: Relevance
“…Medical practitioners who had experience in collaborating with a NP were significantly more likely to disagree that NPs provide low-quality primary health care, and more likely to support NP prescribing, consider that NPs can attract new patients, agree that patients accept NPs and believe that NPs free up MP time [77,78]. In Carr et al’s survey 100% of the GPs who worked with a NP agreed that NP should work in primary health care compared to 89% of the GPs who did not [76].…”
Section: Resultsmentioning
confidence: 99%
“…Medical practitioners who had experience in collaborating with a NP were significantly more likely to disagree that NPs provide low-quality primary health care, and more likely to support NP prescribing, consider that NPs can attract new patients, agree that patients accept NPs and believe that NPs free up MP time [77,78]. In Carr et al’s survey 100% of the GPs who worked with a NP agreed that NP should work in primary health care compared to 89% of the GPs who did not [76].…”
Section: Resultsmentioning
confidence: 99%
“…4 Faculty concerns included perceived additional teaching load, cost-effectiveness of employing dental therapists, and the ability of dental therapists to improve access to care to underserved groups on government programs. [10][11][12][13][14] If these motivators occur with dental faculty, attitudes toward dental therapy and dental therapy students should become more favorable over time. These findings were consistent with the results of other studies that found little support for dental therapy among all Minnesota and U.S. dentists.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Earlier studies on nurse practitioners and physician assistants suggested physicians were more likely to accept those professionals when they worked with them, were familiar with their role, and understood how they benefited patient care. [10][11][12][13][14] If these motivators occur with dental faculty, attitudes toward dental therapy and dental therapy students should become more favorable over time. This potential has particular promise at the University of Minnesota School of Dentistry as dental therapy students take courses with either dental students or dental hygiene students, and sometimes all three student groups are in the same course under the instruction of the same faculty members.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, permitiu investigar o objeto de pesquisa na perspectiva da gestão central e no âm-bito das UBS e seus trabalhadores. As taxas de resposta dos secretários municipais, Coordenadores da Atenção Básica ou da Estratégia Saúde da Família e retorno dos formulários de fonte documental superaram as expectativas quando comparadas às de outros estudos em saúde pú-blica que também utilizaram instrumentos autoaplicados 21,22 .…”
Section: Discussionunclassified